Geographical Inquiry with Geospatial Virtual Panoramic: Can Improve the Spatial Skills of Geography Students? - Bayu Dwi Saputro; Alfyananda Kurnia Putra; Lestari Rahayu (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2023)
ABSTRACT Thinking spatial is essential for students to develop in geography learning. This is useful for students to analyze geosphere phenomena from a spatial perspective. The selection of a learning model is critical to develop students' abilities. However, the ability to think spatially in class XII IPS 2 MAN Kota Blitar is still low. A students' spatial thinking skills in the pre-cycle, namely 43.77. One of the reasons for this lack of spatial thinking skills is that teachers lack innovation in using instructional media and often use the lecture method. This research aims to improve learning and students' spatial thinking skills by applying the geographic inquiry model with the help of a virtual panoramic geospatial. The type of research used is Classroom Action Research (CAR), which is divided into two cycles with descriptive quantitative analysis. The results show that after applying the geographical inquiry model with the help of a panoramic virtual geospatial, the spatial thinking ability test score for cycle 1 was 64.76, and cycle 2 was 77.56. This indicates that students' spatial thinking skills always increase every cycle. Implementing the geographic inquiry model, assisted by a virtual panoramic geospatial, can help students better interpret a geographical phenomenon from a spatial perspective.Â Keywords: Spatial thinking skills; Geographical Inquiry; Geospatial virtual panoramic.